Bibliometrics review: Research focus on dribbling in soccer from the database scopus (2008-2022) - Muhammad Irfan; Leni apriani; Oki Candra (Universitas Riau, 2023)
(English)Dribbling the ball is the initial ability that must be mastered by football players, players must be able to control the ball when moving, standing or preparing to make a pass or shot at goal. The purpose of this study is to provide a clear picture of the research that has been conducted and emerging trends in the research focus on dribbling in soccer. This research is a literature review research, there are 43 publications refined with 4 stages (identification, screening, eligibility, inclusion) from the Scopus database which are then analyzed using the bibliometric analysis method assisted by the Vosviewer application. The results of the research show that the publication is related to dribbling skill in football peaked with the highest number of publications in 2007. Publications in 2015 have been cited more than any other year. Most of the publications related to this field have been published in Q1 journals. England and Portugal are countries that have a great influence on research in this field. The research focus is divided into three, namely, 1) soccer players, performance and speed; 2) dribbling skill, age, and control; 3) training, change and coach. The new theme in this field is football player, approach, dribbling test, and sports class. Keyword dribbling the skills that are the focus of the first research as well as the theme in this study do not have a direct link to keywords passing and measure, meaning that there is no research that directly links dribline skill and passing and measure together.(Indonesian)Menggiring bola merupakan kemampuan awal yang harus dikuasai oleh pemain sepak bola, pemain harus dapat menguasai bola pada saat bergerak, berdiri atau bersiap melakukan operan atau melakukan tembakan ke gawang. Tujuan dari penelitian ini adalah untuk memberikan gambaran yang jelas tentang penelitian yang telah dilakukan dan tren yang muncul dalam fokus penelitian tentang dribbling dalam sepak bola. Penelitian ini merupakan penelitian literatur review, terdapat 43 publikasi yang disemurnakan dengan 4 tahapan (identifikasi, screening, kelayakan, inclusi) dari database Scopus yang kemudian dianalisis menggunakan metode analisis bibliometrik berbantuan aplikasi Vosviewer. Hasil penelitian menunjukkan bahwa publikasi terkait keterampilan dribbling dalam sepakbola memuncak dengan jumlah publikasi tertinggi pada tahun 2007. Publikasi pada tahun 2015 paling banyak disitasi dibandingkan tahun lainnya. Sebagian besar publikasi yang terkait dengan bidang ini telah dipublikasikan di jurnal Q1. Inggris dan Portugal adalah negara yang memiliki pengaruh besar terhadap penelitian di bidang ini. Fokus penelitian dibagi menjadi tiga yaitu, 1) pemain sepak bola, performa dan kecepatan; 2) keterampilan dribbling, usia, dan kontrol; 3) pelatihan, perubahan dan pelatih. Tema baru dalam bidang ini adalah pemain sepak bola, pendekatan, tes dribbling, dan kelas olahraga. Kata kunci dribbling skill yang menjadi fokus penelitian pertama sekaligus tema dalam penelitian ini tidak memiliki kaitan langsung dengan kata kunci passing dan measure, artinya belum ada penelitian yang secara langsung mengaitkan skill dribline dan passing and measure secara bersama-sama.Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.